Good vs. Bad: An Empirical Analysis of the Brand Names of Coronavirus Vaccines - Kovács, László (HERMES - Journal of Language and Communication in Business, 2024)
Brand names are assets in marketing: a good name can help to sell products. Although research has made several recommendations on how “good” brand names should be created, the complex process is not easily adapted to every product category. Little research is done on a particular product category: the brand names of vaccines. This paper contributes to vaccine brand names in light of the coronavirus pandemic. The theoretical part of the paper first describes the characteristics of “good” and “bad” brand names, and then the focus is narrowed down to the characteristics of drug brand names and to the processes that influenced the naming of coronavirus vaccines. In the empirical part of the paper, Hungarian students perform brand recognition, recall, and association tasks connected to vaccine brand names. It will be shown that the vaccines are known by their public brand names (e.g., Pfizer) and not by their actual brand names (e.g., Comirnaty). The rating of the brand names shows that public brand names are considered to be better than the actual brand names, while brand associations collected for the actual brand names show mixed results. In the last part of the paper, theoretical implications are discussed, and recommendations for pharmaceutical companies are formulated to show what steps these companies could take to overcome the impasse between public and actual brand names.